Peningkatan Protein dan Vitamin B melalui Pemberian Whey dan Lerry pada Produk Nata - Indhira Shagti (JURNAL INFO KESEHATAN, 2017)
Background: Rinse or rice water lyri and whey tofu is a waste generated by many households and home industries are thrown away. Whereas this waste is still a lot of nutrients that still exist such as carbohydrates, proteins, and vitamins. Waste lerri and whey know this can still be utilized to nata by using bacteria Acetobacter xylinum, so it is expected can also increase economic value of society. Objective: To know the effect of whey tofu substitution on thickness, nutrient content and vitamin B1 nata de lerri. Method: This research is purely experimental, using Completely Randomized Design (RAL) consisting of 5 treatments and each repeated 3 times. Where the free variable is media formula nata, namely rice water washing medium (lerri) and whey knows F1 (100: 0)%; F2 (75: 25)%; F3 (50: 50)%; F4 (25: 75)%; F5 (0: 100)%. The dependent variable is nata thickness, nata nutritional value (moisture content, crude protein content, coarse fiber content, vitamin B1) and organoleptic receiving power. Result: In this research there are five formula of nata de lerri substitution whey know that do. But in practice 2 formulas did not work, namely F4 and F5, because the product remains liquid and cloudy white. This is possible fungal contamination that occurs due to a technical error (less sterile). For thickness nata de lerri, the highest result is the formula F1 with a thickness of 1 cm and the lowest F3 with a thickness of 0.5 cm. But for the results of testing the water content, ash content and highest crude protein content is F3 with a water content value 99.93%, ash 0.34%, crude protein content 1.35%. But from the test results of vitamin B1 all formula and water lerri not detected, this is possible because of the error of the test equipment.